Integrated traditional Chinese and western medicine nursing of a patient undergoing toe amputation for diabetic foot ulcers (1例糖尿病足截趾术后患者的中西医结合护理体会) - TONG Fenfei (仝粉飞); ZHI Hui (智慧); LIU Jinjing (刘津京); ZHENG Wen (郑雯) (Association of Integrative Nursing, 2023)
This paper summarized the integrated traditional Chinese and western medicine nursing of a patient undergoing toe amputation for diabetic foot ulcers. Comprehensive nursing interventions including low extremity position care, medication care, pain control and health education were enhanced after toe amputation for diabetic foot ulcers. Based on the Traditional Chinese Medicine syndrome differentiation, Traditional Chinese Medicine ointment rubbing, Tuina on meridian and acupoints, five-element music therapy were carried out to relieve pain, eliminate lower limb swelling, promote wound healing, reduce the incidence of local infection and complications, improve peripheral circulation and neurotrophic status, improve patients' self-care ability and quality of life. . (本文总结1例糖尿病足截趾术后患者的中西医结合护理经验。术后在加强下肢体位护理、针对性用药指导、疼痛护理、健康宣教等护理措施基础上, 基于辨证施护, 开展中药膏摩、经穴推拿、五音疗法等中医疗法, 旨在缓解疼痛, 消除下肢肿胀, 促进创面愈合, 降低局部感染及并发症发生率, 改善患者周围循环及神经营养状态, 提高患者自理能力及生活质量。)